Analisis Pendapatan Petani Jagung Pemelihara Kuda Di Desa Pinabetengan Kecamatan Tompaso Barat Kabupaten Minahasa - Sondakh, Jenifer Kapriati; Jocom, Sherly Gladys; Sondakh, Mex Frans Lodwyk (AGRI-SOSIOEKONOMI, 2023)
The research objective was to analyze the income of maize farmers who raise horses in Pinabetengan Village, West Tompaso District, Minahasa Regency. The research was conducted from August to October 2021, starting from preparation until the preparation of the research report. The research was conducted in Pinabetengan Village, West Tompaso District, Minahasa Regency. The data sources used in this research are primary data obtained directly from respondents of horse keeping corn farmers in Pinabetengan Village, West Tompaso District, Minahasa Regency and asking questions that have been prepared previously. As well as secondary data obtained from relevant institutions or agencies such as the Pinabetengan Village Office, the West Tompaso District Agricultural Extension Office (BPP), and other scientific literature. The sampling method was carried out with a simple random method (purposive sampling), as many as 10 respondents of corn farmers who raise horses in Pinabetengan Village, West Tompaso District, Minahasa Regency. Data analysis used is descriptive statistical analysis by calculating the average income, and tabulating the data. Based on the results of the study it can be concluded that the income of horse-breeding corn farmers in Pinabetengan Village, West Tompaso District, Minahasa Regency amounted to IDR11.719.150 per farmer in one growing season. This income is a large amount for corn farmers and their families in Pinabetengan Village, West Tompaso Subdistrict, Minahasa Regency. The income is turned back into the business and the family life of the farmers.